Construction industry an important pillar of the economy: Investment assistance taking effect - Martin Gornig; Claus Michelsen; Laura Pagenhardt (DIW Weekly Report, 2020)
The construction industry is increasingly becoming a key pillar of the business cycle in Germany. DIW Berlin's construction volume calculation indicates a real expansion of construction services by around three percent each year over the next two years. In nominal terms, sales in the construction industry and its related sectors will grow by around 6.5 percent in 2020 and almost six percent in 2021. Residential construction remains the cornerstone of the upswing, but construction activity in the public sector will also expand significantly over the next two years. Due to the current weak state of the economy, commercial construction is developing somewhat less dynamically. A long-term investment program would be a sound method of increasing growth potential; it would also improve business prospects in the construction industry for the foreseeable future and make the industry more willing to increase construction capacity.
Keywords: E32; E66; 330; construction industry; residential construction; public infrastructure; economic outlook